MIRROR OF THE DARKEST NIGHT - MAHASWETA DEVI; SHAMYA DASGUPTA (CALCUTTA SEAGULL BOOKS, 2018)
It's the mid-to-late 1800s and the British have banished Wajid Ali Shah--the Nawab of Awadh in Lucknow--to Calcutta. To the sound of the soulful melody of the sarangi, the mercurial courtesan Laayl-e Aasman is playing a dangerous game of love, loyalty, deception, and betrayal. ...
Keywords: BENGALI NOVEL -ENGLISH TRANSLATION